RETORIKA MEDIA TENTANG TOLERANSI ANTARUMAT BERAGAMA: ANALISIS WACANA PADA BERITA-BERITA BERTOPIK TOLERANSI AGAMA PADA SITUS PEMBERITAAN DETIK.COM DAN KOMPAS.COM - Lukmantoro, Triyono (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research is motivated by a number of intolerance that occurred in Indonesia. The persons who are victims in the incident was a religious minority. The purpose of the study was to describe the themes of rhetoric displayed by Detik.com and Kompas.com in highlighting cases of Shia Sampang, Madura , which became one of the events among religious intolerance. In addition, this study aims to outline the techniques of journalism and language used by Detik.com and Kompas.com in running the rhetoric of religious tolerance. Results of this study indicate that the themes presented Detik.com is the root problem, the solution, and the attitude of the government; relocate or expel refugees; rejection by majority and resistance reactions by minority, as well as punished minorities and the majority were released. Meanwhile , the themes presented by Kompas.com rhetoric is a lawsuit against the government's attitude; refugees want to return home; Shias forced repent and Religious Affairs Minister refused reconciliation.